Preventative strategies of VAP: Lessons from a one year retrospective study - Mohd Ali, Noor Azizah; Jauncey-Cooke, Jacqueline; Ballard, Emma; Bogossian, Fiona (2017)
Introduction: Ventilator-associated pneumonia (VAP) is a largely preventable complication of mechanical ventilation. Little is known about the current status of the VAP preventive strategies in a paediatric setting.